2006
DOI: 10.1002/ccd.20675
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of a pressure sensor guidewire to measure bileaflet mechanical valve gradients: Hemodynamic and echocardiographic sequelae

Abstract: Suspected prosthetic valve dysfunction is a difficult clinical problem, because of the high risk of repeat valvular surgery. Echocardiographic measurements of prosthetic valvular dysfunction can be misleading, especially with bileaflet valves. Direct measurement of trans-valvular gradients is problematic because of potentially serious catheter entrapment issues. We report a case in which a high-fidelity pressure sensor angioplasty guidewire was used to cross prosthetic mitral and aortic valves in a patient, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
(10 reference statements)
1
8
0
Order By: Relevance
“…The use of coronary pressure wire was described by Fusman et al and Bae et al for native valves Five previously described cases showed use of this coronary pressure wire in patients with bileaflet St. Jude (4 cases) and single tilting disc Bjork‐Shiley (1 case) mechanical AoV for assessment of trans‐valvular gradient (Table ). Compared to large plastic‐coated standard angiography catheters, the coronary pressure wire is very low profile with a 0.014" diameter, which makes it easy to maneuver through double disc mechanical valves without apparent risk of entrapment in the space between the closed discs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of coronary pressure wire was described by Fusman et al and Bae et al for native valves Five previously described cases showed use of this coronary pressure wire in patients with bileaflet St. Jude (4 cases) and single tilting disc Bjork‐Shiley (1 case) mechanical AoV for assessment of trans‐valvular gradient (Table ). Compared to large plastic‐coated standard angiography catheters, the coronary pressure wire is very low profile with a 0.014" diameter, which makes it easy to maneuver through double disc mechanical valves without apparent risk of entrapment in the space between the closed discs.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to large plastic‐coated standard angiography catheters, the coronary pressure wire is very low profile with a 0.014" diameter, which makes it easy to maneuver through double disc mechanical valves without apparent risk of entrapment in the space between the closed discs. In cases by Doorey et al and Khouzam et al, the use of FFR pressure wire across the St. Jude double disc aortic prosthesis in 67 year‐old female and 65‐year‐old male, respectively, and led the authors to confirm low trans‐valvular gradients and defer the redo surgery . In a case series presented by Owan et al of 45 year‐old female and 32 year‐old female with respective St. Jude bileaflet and Bjork‐Shiley AoV prostheses safe and effective use of coronary pressure wire helped identify high transvalvular gradient in severely stenosed AoV prosthesis and help authors decide to send patient for redo surgery .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This initial publication demonstrated that left ventricular pressures measured with this technique were the same as measurements of LV pressure obtained by transseptal technique . This initial publication was followed by a report in which the pressure‐sensing wire technique was utilized in the hemodynamic assessment of a patient with St. Jude bileaflet mechanical aortic and mitral valves . These authors reported that mild aortic insufficiency developed during continuous transthoracic echocardiography while the pressure‐sensing wire was across the mechanical aortic valve and resolved with removal of the wire .…”
Section: Introductionmentioning
confidence: 95%
“…This initial publication was followed by a report in which the pressure‐sensing wire technique was utilized in the hemodynamic assessment of a patient with St. Jude bileaflet mechanical aortic and mitral valves . These authors reported that mild aortic insufficiency developed during continuous transthoracic echocardiography while the pressure‐sensing wire was across the mechanical aortic valve and resolved with removal of the wire . This paper also described the use of the 0.014 inch pressure wire technique to cross a bileaflet mechanical mitral valve via a transseptal approach .…”
Section: Introductionmentioning
confidence: 99%